USING CHATGPT IN UNIVERSITY ACADEMIC WRITING: A BIBLIOMETRIC REVIEW STUDY ON THE IMPLICATIONS FOR WRITING REPORTS, PAPERS, ESSAYS, AND THESES - ADAUTO MEDINA, WILLY ANDRÉS (2024)
THE USE OF CHATGPT IN UNIVERSITY ACADEMIC WRITING HAS GENERATED A GROWING DEBATE ABOUT ITS IMPLICATIONS FOR THE ORIGINALITY, QUALITY, AND AUTHENTICITY OF UNIVERSITY WRITING. ITS ACCELERATED ADOPTION IN THE CREATION OF REPORTS, ESSAYS, AND THESES RAISES SERIOUS QUESTIONS ABOUT ACADEMIC INTEGRITY, THE POSSIBLE INCREASE IN PLAGIARISM, AND THE POTENTIAL DECREASE IN CRITICAL WRITING SKILLS AMONG STUDENTS. THIS BIBLIOMETRIC REVIEW STUDY ANALYZES THE IMPLICATIONS OF THE USE OF CHATGPT IN UNIVERSITY ACADEMIC WRITING, COVERING BOTH BIBLIOMETRIC INDICATORS AND A QUALITATIVE ANALYSIS TO IDENTIFY THE AREAS ON WHICH RESEARCH IN THIS FIELD HAS BEEN FOCUSED. A MIXED AND DESCRIPTIVE APPROACH IS EMPLOYED, BASED ON 71 MANUSCRIPTS REVIEWED AND EXTRACTED FROM THE SCOPUS DATABASE. THE IMPLICATIONS OF THE USE OF CHATGPT ARE IDENTIFIED AND DISTRIBUTED IN THREE AREAS CATEGORIZED AS “QUALITY AND DEVELOPMENT OF WRITING SKILLS”, “ACADEMIC INTEGRITY AND ETHICS IN WRITING”, AND “EDUCATIONAL ASSESSMENT”. DESPITE THE OBSERVED BENEFITS, SUCH AS IMPROVED FLUENCY AND GRAMMAR, SIGNIFICANT CONCERNS REMAIN REGARDING THE OVER-RELIANCE ON CHATGPT AND ITS IMPACT ON STUDENTS’ CRITICAL THINKING SKILLS. IT IS THEREFORE CONCLUDED THAT, ALTHOUGH CHATGPT CAN COMPLEMENT CERTAIN ASPECTS OF ACADEMIC WRITING, IT IS ESSENTIAL FOR STUDENTS TO STRENGTHEN THEIR OWN WRITING SKILLS TO AVOID TOTAL DEPENDENCE ON AI SUPPORT. FURTHERMORE, EDUCATIONAL INSTITUTIONS NEED TO ESTABLISH CLEAR POLICIES AND GUIDELINES ON THE USE OF CHATGPT TO ENSURE ACADEMIC INTEGRITY. IT IS ALSO RECOMMENDED THAT FUTURE STUDIES SHOULD EVALUATE THE EFFECTIVENESS OF THESE POLICIES AND EXPLORE THEIR IMPACT ON THE DEVELOPMENT OF CRITICAL AND CREATIVE SKILLS IN STUDENTS. ©AUTHORS.